Re-acculturation and adaptation among adolescents from returned portuguese immigrant families - Felix Neto (2012)
The aims of this study were to investigate the degree of psychological and sociocultural adaptation among adolescents from returned Portuguese immigrant families and the factors that may predict adaptation. The study sample consisted of 360 adolescents from returned Portuguese immigrant families who answered a self-report questionnaire. A control group involving 217 Portuguese youths was also included in the study. Adolescents from returned immigrant families revealed similar levels of psychological adaptation and better sociocultural adaptation in comparison with peers who have never migrated. Predictive factorssociodemographic and intercultural contact variableswere significantly linked to youths' adaptation. It is concluded that perceived discrimination plays an essential role in re-acculturation outcomes.